Modifikasi Fuel Filter Pada Backhoe Loader 570 SV Untuk Meminimalisir Kerusakan Pada Sistem Bahan Bakar - Irawan Ardiansyah; Sunaryo; Indra Hasan (Journal of Management and Industrial Engineering (JMIE), 2024)
An efficient and reliable fuel system is key to maintaining optimal performance of construction machinery, and fuel filters play an important role in maintaining fuel quality and preventing contaminants from entering the system. In this research, modifications were made to the fuel filter with a focus on increasing filtering efficiency and contaminant retention capacity. Modifications involve the use of more effective filter materials, and increased dirt retention capacity. Experimental methods were used to evaluate the performance of the modified fuel filter, through field trials. Field trial results show that the modified fuel filter is able to increase filtration efficiency and has a higher contaminant retention capacity compared to the original filter, and the modified fuel filter is successful in improving the overall performance of the 570 SV backhoe loader engine, by reducing the risk of damage to the fuel system and improve machine responsiveness.